Linking modes of research to their scientific and societal outcomes. Evidence from 81 sustainability-oriented research projects. Issue 101 (November 2019) - Newig, Jens; Jahn, Stephanie; Lang, Daniel J.; Kahle, Judith; Bergmann, Matthias
Highlights: We test how different research modes influence societal and academic outcomes. Early Involvement of non-academic actors appears to benefit societal project outcomes. Academic performance is lower in projects with non-academic actor involvement. Careful project design may reduce trade-offs between academic and societal outcomes. Abstract: Sustainability-oriented research has increasingly adopted "new" modes of research promoted under labels such as 'post-normal science', 'mode 2 knowledge production' or 'transdisciplinarity', aiming to address societally relevant problems and to produce 'socially robust' knowledge by involving relevant scientific disciplines and non-academic actors into the research. We present the results of a comparative quantitative analysis of 81 completed sustainability-oriented research projects, coupled with an in-depth study of six projects, to empirically investigate the assumed connections between research modes and societal and academic project outcomes. Statistical analysis suggests that contributions from practitioners in early phases of research projects positively influence certain societal and practice-relevant outcomes. By contrast, including non-academic actors and practitioner knowledge into research negatively impacts academic outputs and citations, indicating a trade-off between academic and societal impacts. Yet projects which apply structured methods of knowledge integration score generally higher on academic outputs and citations. Moreover, the funding context affects both research mode and research outcomes. Finally, practitioner involvement negatively affects completing of PhD projects. Findings from the in-depth study reinforce a trade-off between the societal and academic impact of interdisciplinary and transdisciplinary sustainability-oriented research. We find that projects which had a double research objective on academic and societal outcomes but which did not specify how to realize both, neglected either the academic or the societal impact during the research process. Moreover, we find that a well-designed combination of disciplinary as well as inter- and transdisciplinary project phases helped projects to meet both demands.